Influence of Floral Strip Width on Spider and Carabid Beetle Communities in Maize Fields - Jia-Lu Li; Lan-Mei Huang; Zi-Yi Xiang; Jian-Ning Zhao; Dian-Lin Yang; Hui Wang; Yan-Jun Zhang (Insects)
The study explored the impact of floral strip width on the spider and carabid beetle communities in maize fields over two years. Three widths of floral strips (2 m, 4 m, and 6 m) were compared with maize-only control strips to evaluate species diversity and distribution. The results showed significant differences in both spider and carabid populations between floral and control strips, with 4 m and 6 m widths consistently harboring higher biodiversity. The results also showed distinct community clustering within floral strips in 2021, which became more cohesive by 2022. Further analysis validated significant community dissimilarities between different strip widths and controls, highlighting the ecological advantages of wider floral strips for enhancing natural enemy biodiversity. Spider activity density was notably higher in floral strips than in adjacent farmland, peaking at the edges of 4 m-wide strips and decreasing in 6 m-wide strips, with the lowest density in 2 m-wide strips. Carabid beetle activity density varied considerably with strip width and proximity to the edge, typically peaking at the edges of wider strips. Spiders were more responsive to strip width than carabid beetles. Based on these findings, we suggest using 4 m- or 6 m-wide floral strips to enhance biodiversity and natural pest control in agricultural landscapes; the floral strips narrower than 4 m (such as 2 m) could not support optimal biodiversity, as spiders and carabid beetles do not disperse far into the maize field, with spiders having dispersal distances of less than 3 m and carabid beetles less than 10 m. Vegetation characteristics significantly influenced spider and carabid communities, impacting species richness, diversity indices, and community structures across two study years. These insights highlight the necessity of thoughtfully designing floral strips to enhance biodiversity and natural pest control in agricultural landscapes.